Cancer modeling by Transgene Electroporation in Adult Zebrafish (TEAZ) - Scott J. Callahan; Stephanie Tepan; Yan M. Zhang; Helen Lindsay; Alexa Burger; Nathaniel R. Campbell; Isabella S. Kim; Travis J. Hollmann; Lorenz Studer; Christian Mosimann; Richard M. White (The Company of Biologists, 2018)
Transgenic animals are invaluable for modeling cancer genomics, but often require complex crosses of multiple germline alleles to obtain the desired combinations. Zebrafish models have advantages in that transgenes can be rapidly tested by mosaic expression, but typically lack spatial and temporal control of tumor onset, which limits their utility for the study of tumor progression and metastasis. To overcome these limitations, we have developed a method referred to as Transgene Electroporation in Adult Zebrafish (TEAZ). TEAZ can deliver DNA constructs with promoter elements of interest to drive fluorophores, oncogenes or CRISPR-Cas9-based mutagenic cassettes in specific cell types. Using TEAZ, we created a highly aggressive melanoma model via Cas9-mediated inactivation of Rb1 in the context of BRAFV600E in spatially constrained melanocytes. Unlike prior models that take ∼4 months to develop, we found that TEAZ leads to tumor onset in ∼7 weeks, and these tumors develop in fully immunocompetent animals. As the resulting tumors initiated at highly defined locations, we could track their progression via fluorescence, and documented deep invasion into tissues and metastatic deposits. TEAZ can be deployed to other tissues and cell types, such as the heart, with the use of suitable transgenic promoters. The versatility of TEAZ makes it widely accessible for rapid modeling of somatic gene alterations and cancer progression at a scale not achievable in other in vivo systems.